2013
DOI: 10.1128/aac.00381-13
|View full text |Cite
|
Sign up to set email alerts
|

Bulky “Gatekeeper” Residue Changes the Cosubstrate Specificity of Aminoglycoside 2″-Phosphotransferase IIa

Abstract: A minoglycoside antibiotics are broad-spectrum compounds used for treatment of serious infections caused by both Grampositive and Gram-negative bacterial pathogens (1). The major mechanism of aminoglycoside resistance in Gram-positive and Gram-negative bacteria is the production of aminoglycosidemodifying enzymes, aminoglycoside phosphotransferases (APHs; also known as aminoglycoside kinases), aminoglycoside acetyltransferases, and aminoglycoside nucleotidyltransferases. These enzymes modify hydroxyl or amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In exclusive GTP-specific isoforms, Tyr blocks entry of ATP; thus, adding the Tyr gatekeeper residue to ATP-specific isoforms resulted in a high GTP affinity. 29 Computational analysis of DNA polymerase μ with its cognate and noncognate ligands has suggested the role of gatekeeper residues in tightening the nucleotide binding pocket, which in turn alters the electrostatic potential, in addition to active site distortion by crucial residues. 30 In β-lactamase (BlaC), Ile 105 acted as a gatekeeper residue controlling access of the substrate to active site.…”
Section: Discussionmentioning
confidence: 99%
“…In exclusive GTP-specific isoforms, Tyr blocks entry of ATP; thus, adding the Tyr gatekeeper residue to ATP-specific isoforms resulted in a high GTP affinity. 29 Computational analysis of DNA polymerase μ with its cognate and noncognate ligands has suggested the role of gatekeeper residues in tightening the nucleotide binding pocket, which in turn alters the electrostatic potential, in addition to active site distortion by crucial residues. 30 In β-lactamase (BlaC), Ile 105 acted as a gatekeeper residue controlling access of the substrate to active site.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that removal of the phenolate side chain gives access to the adenine-specificity template and the mutant is able to bind ATP efficiently. The recent kinetic analysis of the M85Y mutant of APH(2 00 )-IIa had the opposite effect, switching the enzyme to a GTPexclusive variant with a more than 300-fold increase in the K m for ATP and a dramatic decrease in catalytic efficiency by three orders of magnitude (Bhattacharya et al, 2013). Here, we observe an interesting phenomenon with the Y100F mutant of APH(2 00 )-Ia, the effect of which is not as clear as the aforementioned mutations, yet which overall produces a mutant enzyme capable of conferring resistance to the aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in APH(2 00 )-IVa the corresponding secondary hydrophobic pocket residues [Val78 and Ala93; APH(2 00 )-IVa residue numbering] are less bulky, and this opens the secondary pocket significantly in this enzyme such that the phenylalanine gatekeeper can be readily accommodated. Structural analysis of the F95Y mutant of APH(2 00 )-IVa showed that the bulkier tyrosine could also be accommodated in the larger secondary pocket (Shi & Berghuis, 2012), and two independent kinetic analyses of F95Y mutants of APH(2 00 )-IVa demonstrate the ability of this mutant to utilize both GTP and ATP as cosubstrates (Shi & Berghuis, 2012;Bhattacharya et al, 2013).…”
Section: The Nucleotide-binding Sitementioning
confidence: 99%
See 2 more Smart Citations